Evaluation of Fire Safety Officer Competencies on the Reliability of Building Fire Protection and Prevention Systems - Achmad Firdaus; Ayomi Dita Rarasati (Journal of International Conference Proceedings (JICP), 2019)
High rise buildings can be a safe place for activities when protected by a reliable fire protection system. Fire safety studies are generally focus on active and passive fire protection systems, life-saving and fire evacuation in a building. This study aims to examine fire protection systems from the fire safety officers’ perspective as an important part to ensure that the protection system can function properly and as an initial responder to fire. This study concludes the needs of fire safety officer in a multi-storey building that absolutely necessary as an element of managing the fire protection system and as an initial responder of fire to minimize the impact of property losses and casualties.